The effectiveness of simplified intervention program for preventing and reducing low back pain among Malaysian bus drivers - Mohd Tamrin, Shamsul Bahri; Yokoyama, Kazuhito; Li, Naing; Ng, Yee Guan (Science Publications, 2014)
An intervention study was conducted in order to determine the effectiveness of an exercise program for reducing Low Back Pain (LBP) among bus drivers. A total of 197 bus drivers were randomly selected from a baseline study involving 1,197 drivers. Repeated Intervention programs (IN1 and IN2) were introduced which consist of a video programs, poster, pamphlet and demonstration. Pre-Intervention (pre-IN1 and pre-IN2) and post Intervention (post-IN1 and post-IN2) assessment studies the effect of the intervention programs to LBP and knowledge of respondents observed every 3 months. Knowledge score during Pre-IN 1 shows no significant difference between both groups whereas significant increase of knowledge was observed in Post-IN1, Pre-IN2 and Post-IN2 among the intervention group. The study revealed no significant changes of LBP complaints after post-IN1 in both group but a significant reduction of LBP among intervention group compared to the control group in the post-IN2. The effectiveness of the program was only seen after 6 months of the program.